Dosing of Mood Stabilizers for Bipolar Disorder Patients in the Research on Asian Psychotropic Prescription Patterns Consortium Study. Issue 3 (6th May 2022) - Wang, Yuxi; Chew, Qian Hui; Lin, Shih-Ku; Yang, Shu-Yu; Ouyang, Wen-Chen; Chen, Chih-Ken; Park, Seon-Cheol; Jang, Ok-Jin; Park, Jun Hyuk; Chee, Kok-Yoon; Ding, Kwong Sen; Chong, Jamaline; et al.
Abstract: Background: Because use and dosing of mood stabilizers (MSs) to treat bipolar disorder (BD) patients in Asia are not well documented, we examined prevalence and clinical correlates of treatment of Asian BD patients with relatively high doses of MSs. Methods: We conducted a pharmacoepidemiological survey across 13 Asian countries and territory in the Research on Asian Psychotropic Prescription Patterns Consortium. Mood stabilizer doses were converted to lithium carbonate equivalents (Li-eq milligrams per day). We compared relatively high (>900 Li-eq mg/day) versus lower MS doses by bivariate comparisons, followed by multivariable linear regression to identify factors associated with higher MS doses. Results: Among 1647 participants, MS dose averaged 584 (confidence interval, 565–603 Li-eq mg/d). Preliminarily, the 13.1% of the subjects given greater than 900 mg/d versus those given lower doses were younger, male, currently hospitalized, not currently depressed, and reported lifetime suicidal ideation; they also received relatively high doses of antipsychotics, received electroconvulsive treatment within the previous 12 months, and had greater ratings of tremors and sedation. By linear regression modeling, the mean proportion given high doses of MS was associated significantly and independently with higher doses of antipsychotics, younger age, male sex, hospitalized, more years of illness, country, higher body mass index, recent electroconvulsive treatment, and being in illness remission. Conclusions: Relatively high doses of MSs for BD are prevalent, but vary markedly among Asian countries, and are particularly likely among young males, ill for many years, and given high doses of antipsychotics or ECT. These characteristics allow better identification of patient profiles that can guide treatment of BD patients.